Reconstruction of moderate-sized soft tissue defects in foot and ankle in children: Free deep inferior epigastric artery perforator flap versus circumflex scapular artery perforator flap. Issue 9 (September 2019) - Sui, Xinlei; Cao, Zheming; Pang, Xiaoyang; He, Jiqiang; Wu, Panfeng; Zhou, Zhengbing; Yu, Fang; Tang, Ju-Yu
Summary: Background: This retrospective study was conducted to compare the outcomes between the free deep inferior epigastric artery perforator (DIEP) flap and the circumflex scapular artery perforator (CSAP) flap in reconstruction of moderate-sized soft tissue defects in the foot and ankle of pediatric patients. Patients and methods: From January 2004 to December 2016, 42 patients, ranging from 2 to 13 years old, underwent foot and ankle reconstruction, with a free DIEP flap in 21 cases and a free CSAP flap in the other 21cases. Results: All the flaps survived. No marked differences were observed in the demographics, flap size, recipient vessels, and overall early or late complication rate ( p  > 0.05). The CSAP group had a shorter operation time (134.3 ± 25 min vs. 202.4 ± 24.3 min, p  < 0.05) and flap harvest time (29.7 ± 8.1 min vs. 52.2 ± 9.8 min, p  < 0.05) than the DIEP group had. In long-term follow-up, the CSAP group showed a lower fat hyperplasia rate (14% vs. 52%, p  < 0.05) and better cosmetic outcomes than the DIEP group did ( p  < 0.05). The functional outcomes had no marked differences ( p  > 0.05). Conclusions: The DIEP flap and the CSAP flap are both good options for foot and ankle reconstruction of moderate-sized defects in pediatric patients. The CSAP flap has a shorter operation time and flap harvest time, a lower fat hyperplasia rate, and better long-term cosmetic outcomes than the DIEP flap does.